Retrospective Review of Outcomes in Patients with Endometriosis and Colonic Segmental Resection (CSR) or Low Anterior Resection (LAR) (Global Journal of Medical Research, 2023)
Objective To further the understanding of long-term outcomes of endometriosis patients requiring colonic segmental resection CSR or low anterior resection LAR To improve counseling of patients with bowel endometriosis Methods Retrospective chart review at a single academic institution between 2000-2018 with 3- year follow-up of patients with CSR LAR for endometriosis 21 patients aged 18-45 at single academic institution between 1 1 2000 and 12 31 2018 with ICD9 10 codes of endometriosis AND CSR LAR were included 9 met criteria for endometriosis as indication for CSR LAR were reviewed Results Pre- and post-operative symptoms were categorized into GI hematochezia dyschezia tenesmus incontinence incomplete evacuation of bowel and pre-operative colonoscopy GYN dysmenorrhea dyspareunia pelvic pain and infertility and GU dysuria frequency urgency incontinence and incomplete emptying